Rabbit IgA Hinges That Resist IgA1 Protease Action Provide Options for Improved IgA-Based Therapeutic Agents - de Sousa-Pereira, Patrícia; Lanning, Dennis K.; Esteves, Pedro J.; Spoerry, Christian; Woof, Jenny M.; Pinheiro, Ana (Frontiers in Immunology, 2022)
Immunoglobulin A provides a major line of defence against pathogens and plays a key role in the maintenance of the commensal microbiota in the intestinal tract. Having been shown to be more effective at tumour cell killing than IgG and strongly active against pathogens present in the mucosae, IgA antibodies have been attracting significant attention in recent years for use as therapeutic antibodies. To improve their therapeutic potential, bioengineered IgA forms with increased serum half-life and neutralizing abilities have been developed but the IgA hinge, which impacts susceptibility to bacterial proteases and ability to bridge between target and effector cells, has not yet been explored. The European rabbit has 15 IgA subclasses with exclusive hinge region motifs and varying lengths, constituting a unique model to evaluate the functional capabilities offered by incorporation of longer IgA hinges into immunoglobulins. Hinge regions from rabbit IgAs, featuring different lengths and sequences, were inserted into human IgA1 heavy chain to substitute the IgA1 hinge. These hinges did not appear to affect antigen binding nor the ability of the engineered chimeric IgA1 to bind and trigger FcαRI, as detected by IgA-mediated cell agglutination and release of superoxide by neutrophils. All rabbit hinge-human IgA1 hybrids were resistant to Clostridrum ramosum IgA protease enzyme digestion, as predicted by the lack of the cleavage site in the rabbit hinges. Some IgA1s featuring long rabbit hinges were cleaved by Neisseria meningitidis IgA1 protease cleavage type 1 or 2 enzymes, despite the lack of the predicted cleavage sites. More interestingly, the hybrid featuring the rabbit IgA15 hinge was not affected by any of the IgA proteases. The IgA15 hinge is longer than that found in human IgA1 and is composed by a unique motif with a stretch of nine consecutive Ser residues. These characteristics allow the preservation of a long hinge, with associated ability to bridge distantly spaced antigens and provide higher avidity binding, while remaining resistant to IgA protease degradation. The data suggest that the rabbit Cα15 hinge represents an interesting alternative hinge sequence for therapeutic human IgA antibodies that remains resistant to proteolytic cleavage.